Combinatorial expression of Lef1, Lhx2, Lhx5, Lhx9, Lmo3, Lmo4, and Prox1 helps to identify comparable subdivisions in the developing hippocampal formation of mouse and chicken - Abellán, Antonio; Desfilis, Ester; Medina, Loreta (Frontiers in Neuroanatomy, 2014)
We carried out a study of the expression patterns of seven developmental regulatory genes (Lef1, Lhx2, Lhx9, Lhx5, Lmo3, Lmo4, and Prox1), in combination with topological position, to identify the medial pallial derivatives, define its major subdivisions, and compare them between mouse and chicken. In both species, the medial pallium is defined as a pallial sector adjacent to the cortical hem and roof plate/choroid tela, showing moderate to strong ventricular zone expression of Lef1, Lhx2, and Lhx9, but not Lhx5. Based on this, the hippocampal formation (indusium griseum, dentate gyrus, Ammon's horn fields, and subiculum), the medial entorhinal cortex, and part of the amygdalo-hippocampal transition area of mouse appeared to derive from the medial pallium. In the chicken, based on the same position and gene expression profile, we propose that the hippocampus (including the V-shaped area), the parahippocampal area (including its caudolateral part), the entorhinal cortex, and the amygdalo-hippocampal transition area are medial pallial derivatives. Moreover, the combinatorial expression of Lef1, Prox1, Lmo4, and Lmo3 allowed the identification of dentate gyrus/CA3-like, CA1/subicular-like, and medial entorhinal-like comparable sectors in mouse and chicken, and point to the existence of mostly conserved molecular networks involved in hippocampal complex development. Notably, while the mouse medial entorhinal cortex derives from the medial pallium (similarly to the hippocampal formation, both being involved in spatial navigation and spatial memory), the lateral entorhinal cortex (involved in processing non-spatial, contextual information) appears to derive from a distinct dorsolateral caudal pallial sector.